Pengaruh Konsentrasi Carboxyl Methyl Cellulose (CMC) Terhadap pH, Total Padatan Terlarut dan Organoleptik Susu Kenari - Passal, Imanuela; Tetelepta, Gilian; Lawalata, Vita N (Pattimura University Ambon Maluku Indonesia, 2023)
This study aims to determine the appropriate Carboxyl Methyl Cellulose (CMC) concentration treatment for canarium nut milk with the best physical and organoleptic characteristics. This study was designed using a completely randomized design of one factorial CMC concentration, which consisted of 4 treatment levels, namely 0.1%, 0.2%, 0.3%, and 0.4%. The results showed that canarium nut milk with a concentration of 0.4% CMC was the best treatment with physical characteristics, namely pH 6.43, total dissolved solids 1.86oBrix. Based on the hedonic quality test, it produced canarium nut milk with a color of 2.8 (like), aroma of 2.7 (like), taste of 3.1 (like), and texture of 1.9 (slightly like).